Rowing Science. The nexus of knowledge and performance (Human Kinetics, 2023)
Master the swing with advice from a class of rowing`s elite. Rowing Science offers serious rowers and coaches the in-depth, evidence-based information needed to optimize rowing skills and elevate performance.